Derivation and external validation of the SHIeLD score for predicting outcome in normotensive pulmonary embolism. (15th April 2019) - Freitas, Pedro; Santos, Ana Rita; Ferreira, António Miguel; Oliveira, Afonso; Gonçalves, Mariana; Corte-Real, Ana; Lameiras, Catarina; Maurício, Joana; Ornelas, Énia; Matos, Clara; Faria, Daniel; Augusto, João; et al.
Abstract: Background: Identifying patients with normotensive pulmonary embolism (PE) who may benefit from thrombolysis remains challenging. We sought to develop and validate a score to predict 30-days PE-related mortality and/or rescue thrombolysis. Methods: We retrospectively assessed 554 patients with normotensive PE. Independent predictors of the studied endpoint were identified from variables available at admission in the emergency department and were used to create a score. The model was validated in 308 patients from a separate hospital. Results: A total of 64 patients died or needed rescue thrombolysis (44 in the derivation cohort). Four independent prognostic factors were identified: S hock index ≥ 1.0 (OR 3.33; 95% CI 1.40–7.93; P = 0.006), H ypoxaem I a by the PaO2 /FiO2 ratio (OR 0.92 per 10 units; 95% CI 0.88–0.97; P < 0.001), L actate (OR 1.38 per mmol/L; 95% CI 1.09–1.75; P = 0.008) and cardiovascular D ysfunction (OR 5.67; 95% CI 2.60–12.33; P < 0.001) – SHIeLD score. In the development cohort, event rates for each risk tercile were 0.0%, 2.2%, and 21.6%. In the validation cohort, corresponding rates were 0.0%, 1.9%, and 14.3%. The C-statistic was 0.90 (95% CI 0.86–0.94, P < 0.001) in the derivation cohort and 0.82 (95% CI 0.75–0.89, P < 0.001) in the validation cohort. Decision curve analysis showed that the SHIeLD score is able to accurately identify more true positive cases than the European Society of Cardiology decision criteria. Conclusions: A risk score to predict 30-days PE-related mortality and/or rescue thrombolysis in patients with normotensive PE was developed and validated. This score may assist physicians in selecting patients for closer monitoring or aggressive treatment strategy. Highlights: Risk stratification in normotensive PE patients is suboptimal. The SHIeLD score predicts 30-days PE-related mortality and/or rescue thrombolysis. This score can identify a subgroup of normotensive PE patients at higher risk. Patients may be selected for closer monitoring or an aggressive treatment strategy.